2014
DOI: 10.1111/neup.12094
|View full text |Cite
|
Sign up to set email alerts
|

Survival of rabid rabbits after intrathecal immunization

Abstract: Rabies is a fatal zoonotic disease for which no effective treatment measures are currently available. Rabies virus (RABV) has anti-apoptotic and anti-inflammatory properties that suppress nerve cell damage and inflammation in the CNS. These features imply that the elimination of RABV from the CNS by appropriate treatment could lead to complete recovery from rabies. Ten rabbits showing neuromuscular symptoms of rabies after subcutaneous (SC) immunization using commercially available vaccine containing inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similar IT vaccination in dogs has been reported by Baer et al, which not only induced VNA in the CSF, but also prolonged the morbidity [ 61 ]. Recent report of survival of rabid rabbits after IT immunization highlights the importance of CSF VNA on viral clearance [ 30 ]. Furthermore, it has recently been demonstrated that the RABV infection can be cleared from the CNS by exogenous administration of VNA in immunocompetent or immunocompromised mice, as long as the BBB permeability is enhanced for the passage of VNA from the periphery to the CNS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar IT vaccination in dogs has been reported by Baer et al, which not only induced VNA in the CSF, but also prolonged the morbidity [ 61 ]. Recent report of survival of rabid rabbits after IT immunization highlights the importance of CSF VNA on viral clearance [ 30 ]. Furthermore, it has recently been demonstrated that the RABV infection can be cleared from the CNS by exogenous administration of VNA in immunocompetent or immunocompromised mice, as long as the BBB permeability is enhanced for the passage of VNA from the periphery to the CNS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown most recently that it is possible to clear an established infection with wt RABV by intravenous administration of VNA in both immunocompromised and immunocompetent mice as long as the BBB permeability is enhanced [ 29 ]. It has also been shown in rabid rabbits that it is possible to reverse the course of infection by intrathecal immunization with attenuated RABV [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the intrathecal inoculation of rabies vaccines directly into the CSF of rabbits showing neuromuscular symptoms of rabies, led to the clearance of RABV from the CNS and their survival [100]. Thus, these studies provide evidence of RBAV clearance from CNS and possible therapy for rabies using intrathecal RABV immunization.…”
Section: Rabies Vaccines and Pepmentioning
confidence: 99%
“…Red cell agglutination at  1:25 was considered positive for the presence of antibody (Harris et al 2009). White Rabbits weighing 3-4 kg were selected for positive and negative testing groups for the developed vaccine for its possible immunogenic reaction in horses (Kesdangsakonwut et al 2014).…”
Section: Sensitivity and Specificity Of Antigenmentioning
confidence: 99%